Carnivalization of the Business World: “The New Woman” in Three Plays by David Mamet - Németh, Lenke (FOCUS: Papers in English Literary and Cultural Studies, 2024)
To Mamet the business world, where his most successful and provocative plays are set, appears to be a quintessential American site. It is into this congenial space that he projects all his worries, concerns and criticism about an America that is portrayed as falling apart. In the context of business Mamet can address nearly all the themes he has been haunted by: the decline of American values, the decay of American idealism, the prevalence of corruption and venality in business, the degradation of the business ethic into deception and betrayal, the loss of the American Dream and of the frontier spirit, urban alienation, the communication breakdown between people, the conflicting and discordant relationship between men and women, women’s place and roles in the shifting ambience of gender expectations. The plays immersed in the world of business (hence “business plays”1) include American Buffalo (1976), which established Mamet as a leading dramatist; the Pulitzer Prizewinning Glengarry Glen Ross (1983); Speed-the-Plow (1987), revealing the corrupt world of the Hollywood film industry; House of Games2 (1987), echoing American Buffalo in the sense that in both plays business is equated with crime; and Oleanna (1992), set in the world of higher education, which is depicted as “a service industry, the intellectual handmaiden of American business” (Watt 1094).